Atomically Dispersed Zn‐Stabilized Niδ+ Enabling Tunable Selectivity for CO2 Hydrogenation. Issue 7 (23rd February 2022) - Wang, Yaning; Feng, Kai; Tian, Jiaming; Zhang, Jiajun; Zhao, Baohuai; Luo, Kai Hong; Yan, Binhang
Abstract: For a heterogeneous catalytic process, the performance of catalysts could be improved by modifying the active metal with a second element. Determining the enhanced mechanism of the second element is essential to the rational design of catalysts. In this work, Zn was introduced as a second element into Ni/ZrO2 for CO2 hydrogenation. In contrast to Ni/ZrO2, the selectivity of NiZn/ZrO2 is observed to shift from CH4 to CO. A series of structural characterization results reveals that Zn is atomically dispersed in the NiO and ZrO2 phases as NiZnO x and ZnZrO x, respectively during CO2 hydrogenation, stabilizing a higher valence state of Ni (Ni δ+ ) under a hydrogenation atmosphere over Ni−O−Zn site and thus promoting the generation of CO. These findings shed light on the O‐mediated bimetallic effect of NiZn/ZrO2 and bring new insight into the rational design of more efficient heterogeneous catalysts. Abstract : Positively stabilized : For CO2 hydrogenation over NiZn/ZrO2 catalysts, Zn is atomically dispersed in NiO and ZrO2 phases as NiZnO x and ZnZrO x, respectively. The formed Ni−O−Zn sites enhance the bonding strength of Ni to the ligand O, stabilizing Ni δ+ under reducing atmosphere. The Ni δ+ species weaken the adsorption and hydrogenation capacity of adsorbed CO and promote the reverse water gas shift reaction.